Neisseria meningitidis serogroup C sepsis and septic arthritis in an HIV-positive man. (August 2017) - Fox-Lewis, A; Eades, CP; Manson, JJ; Morris-Jones, S; Miller, RF
A patient with well-controlled HIV-1 infection presented with fever and rigors, a widespread maculopapular rash, and severe generalised arthralgia. Sepsis of unknown aetiology was diagnosed, and treatment with broad-spectrum antimicrobials commenced. Following initial clinical improvement, a right knee septic arthritis developed. Microscopy and culture of the joint aspirate were negative for organisms but 16S rDNA PCR identified Neisseria meningitidis DNA, subsequently verified as capsular genogroup C, thus confirming a diagnosis of disseminated meningococcal sepsis with secondary septic arthritis.